2018
DOI: 10.1073/pnas.1721241115
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic switch from repressive to permissive chromatin in response to cold stress

Abstract: SignificancePhenotypic adaptations of plants in response to changes in climate are well known to be mediated by molecular mechanisms, including activation or suppression of transcription factors that control target gene expression. However, the chromatin changes that are essential for the binding of transcription factors are much less understood. Gene derepression at the chromatin level is considered to be the starting point for gene transcription. We report a mechanism of gene derepression through which HOS15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
213
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(220 citation statements)
references
References 70 publications
(96 reference statements)
7
213
0
Order By: Relevance
“…Consistent with the previous qPCR-based analysis of COR15A regulation [17], 5 days after 24 h cold priming none of the reference genes for epigenetic cold memories, namely COR15A, COR47 or FLC (Suppl. Table 2) [74,75], showed priming-dependent regulation in the present study.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Consistent with the previous qPCR-based analysis of COR15A regulation [17], 5 days after 24 h cold priming none of the reference genes for epigenetic cold memories, namely COR15A, COR47 or FLC (Suppl. Table 2) [74,75], showed priming-dependent regulation in the present study.…”
Section: Discussionsupporting
confidence: 72%
“…Various studies suggest an epigenetic memory, such as histone and DNA (de-)acetylation or (de-)methylation, for storing information on thermal stress events [15,[71][72][73]. For example, COR15A (At2g42540) and COR47 (At1g20440) are stronger expressed, if the second cold stimulus quickly follows the first one [74]. The majority of the cold-induced histone marks, however, is metastable.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to histone methylation, other histone modifications also play important roles in the cold stress response. Histone acetylation is enriched in the bodies of a number of cold‐responsive genes (Zhu et al 2008; Park et al 2018). This process is dynamically regulated by histone acetyltransferases (HATs) and histone deacetylases (HDACs).…”
Section: Epigenetic Regulation During the Extreme‐temperature Stress mentioning
confidence: 99%
“…Recent studies have indicated that another HD2 family deacetylase, HD2C in Arabidopsis , is involved in CBF‐dependent transcriptional activation of COR genes upon cold stress. HD2C is a target of HIGH EXPRESSION OF OSMOTICALLY RESPONSIVE GENES 15 (HOS15)‐mediated degradation under cold treatment (Park et al 2018). HIGH EXPRESSION OF OSMOTICALLY RESPONSIVE GENES 15 is a component of the CULLIN 4 (CUL4)‐based E3 ubiquitin ligase complex (Zhu et al 2008).…”
Section: Epigenetic Regulation During the Extreme‐temperature Stress mentioning
confidence: 99%
“…At the heart of this regulation is the chaperone activity of the cold shock protein cspA and its 5'UTR that acts as a thermosensor (Giuliodori et al, 2010) and auto-regulates its own abundance in a temperature-dependent way . In plants, cold adaptation is more complex, involving temperature-induced adjustments of the chromatin (Zeng et al, 2019;Park et al, 2018), transcriptional (Nagano et al, 2019), pre-mRNA processing (Calixto et al, 2018), post-transcriptional and posttranslational landscapes (Zhu, 2016). The transcriptional response to cold acclimatization in plants is beginning to be unraveled and entire signaling networks such as the C-repeat binding transcription factor (CBFs) regulon have been exposed (Zhao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%